2020
DOI: 10.3389/fpsyg.2020.01224
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious and Distinctive Control of Vocal Pitch and Timbre During Altered Auditory Feedback

Abstract: Vocal control plays a critical role in smooth social communication. Speakers constantly monitor auditory feedback (AF) and make adjustments when their voices deviate from their intentions. Previous studies have shown that when certain acoustic features of the AF are artificially altered, speakers compensate for this alteration in the opposite direction. However, little is known about how the vocal control system implements compensations for alterations of different acoustic features, and associates them with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 75 publications
(121 reference statements)
2
9
0
Order By: Relevance
“…1 B). The amount of compensation was almost proportional to the amount of seven f o shifts (0, ± 25, ± 50, or ± 100 cents), as already shown in our previous study 36 . We calculated the compensation ratio for each participant, which was defined as a sign-inverted slope of a fitted line to compensation amounts as a function of introduced f o shifts (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1 B). The amount of compensation was almost proportional to the amount of seven f o shifts (0, ± 25, ± 50, or ± 100 cents), as already shown in our previous study 36 . We calculated the compensation ratio for each participant, which was defined as a sign-inverted slope of a fitted line to compensation amounts as a function of introduced f o shifts (Fig.…”
Section: Resultssupporting
confidence: 86%
“…We also assessed other factors that potentially affected the compensation process, such as the perceptual ability to detect a subtle difference in vocal pitch. For this aim, we estimated participants’ ability to detect the f o shifts induced in recorded own voices using a dataset from the listening tests performed in our previous study 36 . In this test, participants were asked to answer whether any pitch modification occurred in the second vocalization compared with the first one in each trial (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown language's utility in identifying ingested drugs and dosages ( 78 ), quantifying depression severity ( 79 ), dissociating and predicting mental illnesses ( 80 82 ), and tracking changes in neurological disease symptoms ( 83 85 ). Given many chronic pain conditions are also neurodegenerative ( 86 ) and linked to changes in cognitive functioning or emotional processing, researchers are investigating whether quantitative language features can also measure pain qualities, although qualitative research investigating pain and language has been around for some time ( 77 , 87 – 90 ). Unlike questionnaires, collecting patient language about their own experience is far less limiting, and whereas numeric PROs could be influenced by various cognitive processes, voice acoustic properties and lower-level linguistic and syntactic structures are harder to consciously influence in the same way ( 91 , 92 ).…”
Section: State-of-the-art In Pain Methodsmentioning
confidence: 99%
“…Some aspects were limited in the harmonizer, considering that the vocal harmonizer shifts the whole frequency spectrum (including associated vowel formants), has no formant correction parameter, and was developed for musical applications and not for voice research. After this product became discontinued, researchers started to use TC Helicon Voice One (Keough et al, 2013) and TC Helicon VoiceWorks Plus (Xu et al, 2020). Both TC Helicon hardware use a similar pitch-shifting algorithm but also have formant correction parameters that can provide additional control over pitch shifting.…”
Section: Introductionmentioning
confidence: 99%